2017
DOI: 10.1111/1748-8583.12173
|View full text |Cite
|
Sign up to set email alerts
|

Supporting team citizenship: The influence of team social resources on team‐level affiliation‐oriented and challenge‐oriented behaviour

Abstract: Using a conservation of resources theoretical framework, we connect within‐team social resources with team‐level citizenship behaviours. In a sample of 385 employees situated in 70 teams from China, we confirm that team social support and team psychological safety interact to influence both affiliation‐oriented (AOCB) and challenge‐oriented (COCB) citizenship. Specifically, the two social resources substitute for one another, such that “either” team social support “or” psychological safety may be sufficient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 41 publications
0
42
0
2
Order By: Relevance
“…With respect to the (behavioral vs. perceptual) form of social support, one study explicitly defined social support as a combination of behaviors and perceptions (Halbesleben, Zellars, Carlson, Perrewé, & Rotondo, 2010), and an equal number defined social support in terms of behaviors ( k = 6: e.g., da Costa, Zhou, & Ferreira, 2018; Quade, Perry, & Hunter, 2019) or perceptions ( k = 6: Halbesleben et al, 2012; Garcia, Ng, Capezio, Restubog, & Tang, 2017). Six studies were vague in delineating the nature of social support (e.g., Campbell, Liao, Chuang, Zhou, & Dong, 2017; Stoverink, Chiaburu, Li, & Zheng, 2018).…”
Section: Social Support At Work: a Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the (behavioral vs. perceptual) form of social support, one study explicitly defined social support as a combination of behaviors and perceptions (Halbesleben, Zellars, Carlson, Perrewé, & Rotondo, 2010), and an equal number defined social support in terms of behaviors ( k = 6: e.g., da Costa, Zhou, & Ferreira, 2018; Quade, Perry, & Hunter, 2019) or perceptions ( k = 6: Halbesleben et al, 2012; Garcia, Ng, Capezio, Restubog, & Tang, 2017). Six studies were vague in delineating the nature of social support (e.g., Campbell, Liao, Chuang, Zhou, & Dong, 2017; Stoverink, Chiaburu, Li, & Zheng, 2018).…”
Section: Social Support At Work: a Review Of The Literaturementioning
confidence: 99%
“…Regarding the source of social support, only a few studies clearly indicated that support was provided by a supervisor ( k = 5: e.g., Hammer, Kossek, Bodner, & Crain, 2013; Munc, Eschleman, & Donnelly, 2017), a team ( k = 1: Stoverink et al, 2018), or coworkers ( k = 1: da Costa et al, 2018). Seven studies (e.g., Halbesleben et al, 2012; Owens, Baker, Sumpter, & Cameron, 2016) vaguely used “others” or “other people” without direct reference to the roles occupied by those others (e.g., supervisors, upper managers, coworkers, friends, and family members).…”
Section: Social Support At Work: a Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, social support influences coping with negative feedback because it provides unique avenues of resource access (Sarason, 1974; Stoverink, Chiaburu, Li, & Zheng, 2018). Others contend that social support broadens resource inventory when unexpected threats or opportunities appear (Feeney & Collins, 2015; Pluut, Ilies, Curşeu, & Liu, 2018).…”
Section: A Goal-setting Framework Of Gritmentioning
confidence: 99%
“…The western supporting social organizations' identity is similar to that of ordinary social organizations, with strong folk and grass roots nature, relatively pure positioning, and more focused support for social organizations. While under the historical and political influence, China's supporting social organizations not only provide support and guidance, but also play the role in transferring government functions and satisfying the demand of social governance [7]. It can be said that the complexity and diversity of China's supporting social organizations are unique.…”
Section: Introductionmentioning
confidence: 99%